The Rescue of State Financial Losses: A New Paradigm of Law Enforcement - Bastian Lubis; Burhan Alsyouf; Hendro Widodo (Jurnal Hukum, 2026)
Corruption causes state losses that hinder the realization of national goals. The criminal justice system, which still relies on a retributive paradigm, has proven incapable of recovering state losses or preventing corruption. The purpose of this study is to analyze the urgency of recovering state losses as the primary focus of addressing corruption crimes and to propose a formulation for state financial savings based on the value of justice. The results show that a retributive approach only exacerbates the burden on the state budget through case handling costs and overcrowding in correctional institutions, while asset recovery from corruptors is disproportionate to the losses suffered. A restorative justice approach that emphasizes the recovery of state losses has the potential to be a more efficient and equitable alternative, in line with practices in countries such as the Netherlands that prioritize recovery of losses and out-of-court settlements. This study offers a novel approach in the form of the need for regulatory reconstruction that allows for the termination of prosecution or the elimination of criminal penalties for perpetrators who return all state losses, representing a paradigm shift from retributive justice to restorative justice.